Faktor Faktor Yang Berhubungan Dengan Perilaku Pemberian ASI Eksklusif Pada Bayi Di Puskesmas Paal X Kota Jambi - Nazrina Safitri; M. Ridwan; Vinna Rahayu Ningsih; Guspianto Guspianto; Sri Astuti Siregar (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2023)
Exclusive breastfeeding is the only good nutrition for the growth and development of infants aged 0-6 months. Based on data from the Central Statistics Agency, the coverage of exclusive breastfeeding in Jambi Province in 2021 is 71.37%. The achievement of exclusive breastfeeding at the Puskesmas Paal X Jambi City in 2019 was 52, 80%, so it was considered still less than the local government target. This is caused by several factors, namely limited knowledge, attitudes, education, duration of work and maternal age, which greatly affect exclusive breastfeeding. This research is a quantitative research with a cross sectional design. The sample was selected by accidental sampling and obtained 63 respondents. Data obtained from filling out questionnaires and interviews were analyzed using univariate and bivariate with chi-square test or Fisher exact. The results of statistical tests obtained several variables related to the behavior of exclusive breastfeeding to infants at the Puskesmas Paal X Jambi City, namely knowledge, attitudes, education, work with p value <0.05. There is no relationship between maternal age and exclusive breastfeeding at the Puskesmas Paal X Jambi City. Factors related to exclusive breastfeeding behavior at Puskesmas Paal X Jambi City are knowledge, attitude, education, work. Meanwhile, the age factor was not associated with exclusive breastfeeding. Keywords: exclusive breastfeeding, knowledge, attitudes, and characteristics of mothers.